Studi Komparatif Pengetahuan Orang Tua Tentang Temper Tantrum yang Diberikan Pendidikan Kesehatan dengan Media Power Point dan Flip Chart - Lala Budi Fitriana; Warda Rizka Apriani (STIKES Karya Husada Kediri, 2019)
Children with temper tantrum will scream and even hurt people around them when what they what is not fulfilled. The lack of parents’ knowledge often results in an inappropriate respond towards a tantrum child, in which 37% parents simply ignore the child and 31% parents tell the child to be quiet. The knowledge increase can be obtained through power point or flipchart media. To compare parents’ knowledge about temper tantrum obtained through health education using power point and flip chart media at ‘Alifa’ integrated Early Childhood Education, Yogyakarta. This is a quasi-experiment research which uses a pretest and posttest non-equivalent control group design. Samples for this research are selected using an accidental sampling technique, which results in 30 parents chosen as respondents. Data analysis is performed using independent t-test. The research instrument used are questionnaires. The mean result of knowledge before and after health education is given using a power point medium is 75.33 ± 9.348 (55 - 85) and 86.33 ± 8.550 (65-100). The mean result of knowledge before and after health education is given using a flip chart medium is 78.33 ± 13.048 (55 - 95) and 86,33 ± 12.459 (65-100). Power point and flip chart media have influence in increasing knowledge, therefore, power point and flip chart media are both effective to increase knowledge.